Pengaruh Corporate Governance terhadap Compliance of Mandatory Disclosure - Faadillah Novia Arisanti; Ayunita Ajengtyas S. Mashuri; Noegrahini Lastiningsih (Penerbit Goodwood, 2022)
Tujuan (Purpose): The purpose is to determine the effect of the corporate governance on compliance of mandatory disclosure in public companies listed on the Indonesia Stock Exchange. Metodologi penelitian (Research methodology): This research is a quantitative type of research. The population are the property, real estate, and building construction sector companies listed on the IDX in 2015-2019. The data were analyzed using multiple linear regression analysis processed with the SPSS 25.0. Hasil (Results): The results showed that the audit committee independence had no effect on compliance of mandatory disclosure, while the board of commissioners, women commissioners, audit committee, managerial ownership and public ownership had an effect on compliance of mandatory disclosure. Limitasi (Limitations): The corporate governance variables refers to the amount of value in quantity, not quality and the measurement of the dependent variable cannot be a definite indicator. Kontribusi (Contribution): The implication is it can be used as a reference for further research and convey the company to pay attention to components that have the potential to affect the company's compliance with applicable regulations.